The Protection Of Islam From Religious Insult In The Context Of Freedom Of Expression - Ainun Syafiqah Rajuddin; Adzidah Yaakob (Universiti Sains Islam Malaysia, 2024)
The purpose of this study is to examine the nature of freedom of expression from three perspectives of laws, namely, international human right law, Malaysian law as well as Islamic law, and its relation in protecting religion of Islam from religious insult. The study argues that there ought to be a legal protection equipped to religion in order to protect religion from being insulted and indirectly to maintain the peace and the public order in the world. The protection cannot be viewed as violation to the freedom of expression but it shall be viewed as one of restrictions to the freedom of expression because no right or freedom is absolute. The findings indicate that the protection to religion from religious insult has never been regarded as a necessary because it clashes with the freedom of expression. Lastly, the study concludes with recommendations on how to strike a balance between the freedom of expression and the right to have religion to be protected as well as a proposal to develop an international anti-blasphemy law protecting all religions and beliefs. By implementing these methods, religion of Islam can be protected from religious insult and peoples can no longer invoke their freedom of expression as an excuse.